Modeling the axial compressive stress-strain behavior of CFRP-confined rectangular RC columns under monotonic and cyclic loading. (1st February 2018) - Isleem, Haytham F.; Wang, Daiyu; Wang, Zhenyu
Highlights: Axial compressive behavior of FRP-confined rectangular RC columns. Influence of aspect ratio and size of cross-sections on column behavior. Analytical investigation and model development for FRP-confined rectangular columns. Stress-strain modeling of FRP-confined rectangular columns under cyclic compression. Abstract: This paper presents a stress-strain model for rectangular reinforced concrete (RC) columns confined with carbon fiber-reinforced polymer (CFRP) composites and subjected to cyclic axial compression. The model is mainly based on experimental observations and results from a series of tests reported in the companion study, in which 24 large-size CFRP-confined rectangular unreinforced and reinforced concrete columns under monotonic and cyclic axial compression were tested. Relative experimental results compiled from the available literature are also used. The test database covers unconfined concrete compressive strengths ranging from 17.6 MPa to 51.5 MPa and cross-sectional side lengths ranging from 90 mm to 400 mm. The proposed stress-strain model is composed of three main components: (1) a monotonic stress-strain model for the envelope curve of cyclic response; (2) a parabolic expression for the unloading path; and (3) a straight line for the reloading path. The model also considers the effects of key parameters including cross-sectional size, aspect ratio, effective rupture strain of the CFRP, and internal longitudinal and hoop steel reinforcement. The performance of the model is finally verified through comparison of predictions made by this model with selected test results, as well as the predictions of more than 20 models of other researchers.